Inovasi Pengolahan Ikan Asin dan Manajemen Limbah Ramah Lingkungan di Kampung Siabang - Erni Purbiyanti; Yulia Sari; Susi Lestari; Utan Sahiro Ritongga; Serly Novita Sari; Jerry Antonio (LOSARI DIGITAL, 2026)
This community service activity was conducted with the Salted Fish Artisans Association in Kampung Siabang, Palembang, which is known as a household-scale salted fish processing center. The main problems faced by the partners include limited knowledge of hygienic practices, suboptimal technical skills in fish preservation, and low awareness of waste management from fish processing activities. This program aimed to improve the community’s knowledge, skills, and attitudes so that the salted fish processing practices become more hygienic, comply with quality standards, and adopt sustainable production principles. The implementation methods included an initial assessment using a pre-test questionnaire, counseling and technical training on hygienic salted fish processing in accordance with the Indonesian National Standard (SNI 8237:2023), hands-on practice of salting and drying techniques, and mentoring on the utilization of fish processing waste into value-added products. The program evaluation was carried out using post-test questionnaires, field observations, and in-depth interviews to assess changes in participants’ knowledge, skills, and attitudes. The results indicate a significant improvement in participants’ knowledge of hygienic practices and quality standards, with an average score increase of more than 20% between the pre-test and post-test. In addition, participants demonstrated improved skills in fish preservation techniques and increased awareness of environmentally friendly waste management through the utilization of fish by-products. The program also encouraged changes in production behavior toward more hygienic and sustainable practices. More broadly, this activity contributed to strengthening the capacity of household-scale salted fish processing enterprises, improving product quality, and creating opportunities to increase community income through more efficient processing and the utilization of economically valuable waste.